Stakeholder Engagement: Past, Present, and Future. Issue 5 (May 2022) - Kujala, Johanna; Sachs, Sybille; Leinonen, Heta; Heikkinen, Anna; Laude, Daniel
Stakeholder engagement has grown into a widely used yet often unclear construct in business and society research. The literature lacks a unified understanding of the essentials of stakeholder engagement, and the fragmented use of the stakeholder engagement construct challenges its development and legitimacy. The purpose of this article is to clarify the construct of stakeholder engagement to unfold the full potential of stakeholder engagement research. We conduct a literature review on 90 articles in leading academic journals focusing on stakeholder engagement in the business and society, management and strategy, and environmental management and environmental policy literatures. We present a descriptive analysis of stakeholder engagement research for a 15-year period, and we identify the moral, strategic, and pragmatic components of stakeholder engagement as well as its aims, activities, and impacts. Moreover, we offer an inclusive stakeholder engagement definition and provide a guide to organizing the research. Finally, we complement the current understanding with a largely overlooked dark side of stakeholder engagement. We conclude with future research avenues for stakeholder engagement research.